P077 SMAD7 shows a biphasic expression pattern during progression of ulcerative colitis-associated colorectal cancer. (25th January 2019) - Chandrasinghe, P; Cereser, B; Moorghen, M; Spaggiari, P; Maroli, A; Del Bel Belluz, L; Hart, A; Spinelli, A; Stebbing, J; Warusavitarne, J
Abstract: Background: Ulcerative colitis (UC) is an idiopathic inflammation of the intestine with an increased risk of developing colitis-associated cancer (CAC). Currently, clinical trials are underway aiming to inhibit SMAD7 to ameliorate inflammation. While the direct effect of depleting SMAD7, an inhibitory molecule in the transforming growth factor-β1 (TGFβ1) pathway, may be therapeutic in UC, its indirect effect on CAC development is largely unknown. TGFβ1 is known to enhance late stages of sporadic colorectal cancers (CRC), where SMAD7 is also elevated. Therefore, we hypothesise that removing inhibition of this pathway by depleting SMAD7 may also be detrimental for CAC. We therefore evaluated the expression of SMAD7 in the colonic epithelium during the inflammation associated neoplastic process to determine a possible role of SMAD7 in CAC. Methods: The expression of SMAD7 protein and mRNA in colonic epithelia was assessed by immunohistochemistry (IHC) and in situ hybridisation (ISH), , respectively, in a cohort of 53 archival colon samples (17 CAC, 12 dysplastic, 12 inflammed, 12 non-neoplastic/non-inflammed) from patients who have undergone colectomies for UC and CAC. The expression within the epithelial cells was evaluated by both digital quantification and validated by blind scoring by a pathologist. Significant differences were tested with one-way ANOVA and Mann–Whitney U test. Results: Cytoplasmic expression of SMAD7 protein is significantly higher in the inflammed epithelium compared with non-inflamed epithelium ( p < 0.0001). Interestingly, a significant decrease of the same was detected in dysplasia ( p = 0.01), although this group is characterised by a higher variability. SMAD7 levels are elevated in cancer compared with dysplasia, suggesting a biphasic expression ( p = 0.009), which could be in part due to the different genetic composition. SMAD7 mRNA expression was not significantly different across different stages of CAC ( p = 0.49). We hypothesise that the lack of correlation between mRNA and protein levels could be attributed to yet unknown post-transcriptional or post-translational regulations. Conclusions: In our cohort of UC affected colon tissues, SMAD7 demonstrated a biphasic expression pattern along the different stages of CAC with peaks during active inflammation and cancer. The increase in SMAD7 expression during neoplastic transformation, comparable to sporadic CRC, may be a protective response of the epithelium to inhibit the effect of TGFβ1. Although inhibiting SMAD7 as a therapy for UC may remit inflammation, we hypothesise it may exacerbate CAC due to further enhancement in TGFβ1 signalling. We envisage further mechanistic studies in vitro, in particular in organoids, could help in understanding the TGFβ superfamily pathway in CAC.